Antimicrobial and antioxidative activities of peptides from goat milk hydrolyzed with various protease - Eni Kusumaningtyas; Raphaella Widiastuti; H. D. Kusumaningrum; M. T. Suhartono (Indonesian Center for Animal Research and Development (ICARD), 2015)
Milk is highly nutritious food containing protein as a good source of bioactive peptide that beneficial for health. This research was aimed to explore potency of bioactive peptide derived from goat milk as an antimicrobial and antioxidant. Milk was hydrolyzed by trypsin, chymotrypsin, pepsin, or protease Bacillus sp. E.13. The peptides obtained were screened for antimicrobial activities through incubation with Staphylococcus aureus, Listeria monocytogenes, Salmonella thyphimurium and Escherichia coli at 106 CFU/mL at 37°C for two hours and plated on Mueller Hinton agar. Antimicrobial activities were determined by comparing the total bacterial colonies to that of bacterial control without peptides addition. Oxidative activity was determined by 2.2’-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid (ABTS) and 2.2-diphenyl-1-picrylhydrazyl (DPPH) assays. Antimicrobial activities were shown in peptides produced from hydrolysis of goat milk protein by pepsin at 37°C, pH 2 for 90 min and by Bacillus sp. E.13 protease at 55°C, pH 11 for 30 and 60 min but the activities were not detected in peptides from hydrolysis by trypsin and chymotrypsin. Peptide from protein hydrolysis by Bacillus sp. E.13 protease could inhibit Listeria monocytogenes, Salmonella thyphimurium and Escherichia coli up to 5 log cycles. The antimicrobial peptides could scavenge ABTS radical up to 86 % and DPPH radical up to 9 % at 68 μg protein/mL. Results indicated that goat milk protein hydrolyzed by Bacillus sp. E.13 protease is potential as antimicrobes and antioxidant.